Potential effectiveness of CM teachers as academic managers - Brasileño, Ma. Rela
The study was undertaken to address the question if teachers of the College of Management make effective academic managers. This was raised in line with the small percentage of CM teachers assigned to hold administrative ranks within the university. Moreover, the research would primarily provide a basis for the academe in the choice of CM teachers who could effectively perform administrative functions. On the survey conducted, a total sample base of 30 teacher-respondents equivalent to the whole population of the College of Management were given questionnaires composed of a large proportion of statements with scoring scheme. It is through this scoring system that the potentials in managerial effectiveness of CM teachers will be determined. The response rate represented 80% of the population. a variety of research techniques were employed in the collection of data, including the analysis and study of UPV annual report, cases, books, college profile and magazine available to researchers. The main data base, however, were the questionnaires administered to the teacher-respondents with a large proportion of statements with scoring schemes. Using statistical tools such as averaging, t-test and F-test, it was determined that CM teachers, as a whole, can also be effective managers. Therefore, the researchers recommend the enhancement of faculty development of CM teachers.